1997
DOI: 10.1046/j.1365-2621.1997.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of recovery conditions on apparent heat resistance of Bacillus stearothermophilus spores

Abstract: The effects of post‐treatment environmental factors on the heat resistance of Bacillus stearothermophilus spores (ATCC 12980, 7953, 15951 and 15952) were investigated. Nutrient Agar (NA), Antibiotic Assay Medium (AAM), Dextrose Tryptone Agar (DTA) and Tryptic Soy Agar (TSA) with Ca2+ added to a final concentration of 100 p.p.m. were used as recovery media. No significant differences were seen between D‐values obtained except in the case of strain 12980 when comparing TSA with the other media and for strain 795… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
5
18
0
Order By: Relevance
“…Previous studies have shown that G. stearothermophilus spores are highly resistant to heat (7,20,26). Similarly, we found that at 85°C the heat treatment D value for G. stearothermophilus spores was remarkably higher than the values for four other species.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies have shown that G. stearothermophilus spores are highly resistant to heat (7,20,26). Similarly, we found that at 85°C the heat treatment D value for G. stearothermophilus spores was remarkably higher than the values for four other species.…”
Section: Discussionsupporting
confidence: 77%
“…G. stearothermophilus usually causes flat sour spoilage of canned liquid foods, such as coffee, during storage in automatic vending machines. Because of the heat resistance of this microorganism's spores, they are often used as a biological indicator to evaluate the effectiveness of sterilization processes (7,20,26). In general, foods are cooked at temperatures around 100°C, and it is assumed that the foods are not damaged by heat treatment at temperatures below 100°C.…”
mentioning
confidence: 99%
“…At 102°C D value (D102°C) for the strain studied LMBCF002 decreased from 4.30 to 0.95min; for pH=7 and pH=4.5 respectively. The result suits those quoted by Lopez et al (1997) and Couvert (1999). The obtained ZpH=3.58 value was close to ZpH reported by Gaillard et al (1998).…”
Section: Studying Ph Effect On B Cereus Heat Resistancesupporting
confidence: 91%
“…The D-values herein obtained at 100 o C were even lower than those found in studies using thermal inactivation at temperatures above 100 o C. Except in the experiments carried out with 0.1 M NaOH, the highest D-value obtained was 2.3 min (Table 1). In contrast, at 120 o C, Lo 'pez et al (1997) reported D-values ranging from 1.32 to 2.84 min, while at 121 o C, Feeherry et al (1987) and Guizelini et al (2012) reported D-values from 1.3 to 5.4 min. Nevertheless, the time required to complete inactivation of G. stearothermophilus spores in the present study was probably, different from those obtained in abovementioned studies.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, the low water content in the core and the intrinsic thermostability of proteins confers to spores of thermophilic species a higher resistant to wet heat than to those of mesophiles (Guizelini et al, 2012). Therefore, the spores of this organism are often used as a biological indicator to assess the effectiveness of sterilization methods (Lo 'pez et al, 1997;Watanabe et al, 2003;Wood et al, 2010).…”
Section: Introductionmentioning
confidence: 99%